The Positioning Problem of Acruvium/Agruvium Road Stop on the Roman Narona–Scodra Road - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper presents data on the positioning problems of Acruvium/Agruvium road stop on the Narona–Scodra road. The question of the position of ancient Acruvium/Agruvium starting from Risan to Budva is one of the unsolved ancient problems. Written historical sources do not state the exact location of the town/settlement. As we can see, there are two prevailing opinions on the position of this town in Boka Kotorska. The advocates of the first opinion put it where today’s Kotor is while the advocates of the second opinion put it closer to the sea, on the territory of the Grbalj district. The question of positioning ancient Acruvium/Agruvium in Boka Kotorska from Risan to Budva presents one of the problems of ancient history and archeology in Montenegro. The contradictions will continue to exist as long as the claims continue to be based exclusively on written historical sources and their analyses without systematic archeological diggings and research. Besides significant number of findings (necropolis, epigraph statues and other material cultural objects) found in Kotor that could support the claims that the ancient Acruvium/Agruvium was actually there, the lack of research in the city center is still an obstacle to fully proving or denying these claims. According to the aforementioned facts, it can be said that the life was ongoing in Kotor and in Grbalj from the ancient times till today. This is proved by archeological findings from both locations. Due to all the aforementioned reasons, it is believed that this question is still open and final conclusions cannot be made.